2022
DOI: 10.1002/cam4.5041
|View full text |Cite
|
Sign up to set email alerts
|

Development of prediction model of low anterior resection syndrome for colorectal cancer patients after surgery based on machine‐learning technique

Abstract: Background Low anterior resection syndrome (LARS) is a common postoperative complication in patients with colorectal cancer, which seriously affects their postoperative quality of life. At present, the aetiology of LARS is still unclear, but some risk factors have been studied. Accurate prediction and early management of medical intervention are keys to improving the quality of life of such high‐risk patients. Objectives Based on machine‐learning methods, this study used the follow‐up results of postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In internal validation, the LASSO-based model achieved the highest AUC of 0.690 among all algorithms. A study 45 used machine learning models, including logistic regression, SVM, decision trees, RF, and ANN, to predict low anterior resection syndrome following CRC resection operation. These authors concluded that logistic regression is the most practical since it has a high sensitivity of 0.911 and can be used as a screening tool for low anterior resection syndrome.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…In internal validation, the LASSO-based model achieved the highest AUC of 0.690 among all algorithms. A study 45 used machine learning models, including logistic regression, SVM, decision trees, RF, and ANN, to predict low anterior resection syndrome following CRC resection operation. These authors concluded that logistic regression is the most practical since it has a high sensitivity of 0.911 and can be used as a screening tool for low anterior resection syndrome.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%